2014
DOI: 10.1111/exd.12517
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress: key promoter of rosacea pathogenesis

Abstract: Recent scientific interest in the pathogenesis of rosacea focuses on abnormally high facial skin levels of cathelicidin and the trypsin-like serine protease kallikrein 5 (KLK5) that cleaves the cathelicidin precursor protein into the bioactive fragment LL-37, which exerts crucial proinflammatory, angiogenic and antimicrobial activities. Furthermore, increased expression of tolllike receptor 2 (TLR2) has been identified in rosacea skin supporting the participation of the innate immune system. Notably, TLRs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 142 publications
0
26
0
Order By: Relevance
“…To date, the mechanisms leading to overproduction of LL‐37 in rosacea have not been fully clarified, but studies have suggested that both the vitamin D and TLR2 pathways are involved. In fact, endoplasmic reticulum stress increases TLR2 expression, leading to overexpression of LL‐37 and kallikrein 5, which mediate rosacea inflammation . In addition, LL‐37 is induced by the vitamin D pathway, and notably, polymorphisms in the vitamin D receptor are associated with rosacea .…”
Section: Role Of Amps/hdps In Human Skin Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the mechanisms leading to overproduction of LL‐37 in rosacea have not been fully clarified, but studies have suggested that both the vitamin D and TLR2 pathways are involved. In fact, endoplasmic reticulum stress increases TLR2 expression, leading to overexpression of LL‐37 and kallikrein 5, which mediate rosacea inflammation . In addition, LL‐37 is induced by the vitamin D pathway, and notably, polymorphisms in the vitamin D receptor are associated with rosacea .…”
Section: Role Of Amps/hdps In Human Skin Diseasesmentioning
confidence: 99%
“…In fact, endoplasmic reticulum stress increases TLR2 expression, leading to overexpression of LL-37 and kallikrein 5, which mediate rosacea inflammation. [116] In addition, LL-37 is induced by the vitamin D pathway, [117] and notably, polymorphisms in the vitamin D receptor are associated with rosacea. [118] Therefore, rosacea predominantly affects the central portions of the face because these areas are permanently exposed to UVB radiation, which activates the vitamin D pathway, resulting in the induction of LL-37.…”
Section: Rosaceamentioning
confidence: 99%
“…Then CIRP relocates to cytoplasm from the nucleus to facilitate the translation of several mRNAs, activating the ERK1/2/MAPK and NF‐κB mediated anti‐apoptotic processes as well as TRX‐mediated anti‐oxidation process. Meanwhile, intracellular unfolded protein response (UPR) is activated to resist the stress‐caused ER stress . As the stress continues, the harmful substrates including ROS and abnormal proteins accumulate in cytoplasm.…”
Section: Action Of Cirp As a Novel Damp In Inflammatory Responsementioning
confidence: 99%
“…Paradoxically, rosacea is most prevalent in individuals with fair skin of European descent, in which vitamin D deficiency is common due to their geographical location. That is why an alternative vitamin D-independent mechanism to promote CAMP expression has been proposed (Melnik, 2014;Melnik, 2016). LL-37 is an important factor in battling infectious agents, including M. tuberculosis; therefore it is possible that these individuals through evolution have developed an alternative vitamin D-independent pathway that activates the CAMP gene promoter.…”
Section: Cathelicidin Antimicrobial Peptide and Atherosclerosismentioning
confidence: 99%
“…This causes phosphorylation of a transcription factor known as CCAAT/enhancer-binding protein alpha (C/EBPa). Phosphorylated C/EBPa binds to a corresponding CAMP promoter region and upregulates the expression of the CAMP gene (Melnik, 2014;2016). ER stress, in response to heat, can also stimulate TRP channels through S1P signaling, thus potentially causing transient erythema (Mair et al, 2011).…”
Section: Endoplasmic Reticulum Stressmentioning
confidence: 99%